2022
DOI: 10.1186/s12879-022-07389-0
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of aerobic exercise on quality of life of people with HIV-associated neurocognitive disorder on antiretroviral therapy: a randomised controlled trial

Abstract: Background HIV-associated neurocognitive disorder (HAND) negatively impacts quality of life (QoL) of people living with HIV who are on antiretroviral therapy (ART). Behavioural intervention adjunct to ART may improve QoL of people with HAND. We determine the effect of a 12-week aerobic exercise programme on QoL in people with HAND who were receiving ART. Trial design This was a parallel-group, randomised controlled trial with concealed allocation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…14 In addition, a recent study of exercise programs has shown that exercise can significantly reduce depression scores. 33 Collectively, the results of this study suggest that AG alone and the therapy of AG combined with AE can alleviate depressive symptoms in MSD patients, and the efficacy of AG + AE may be better than that of AG alone. This is consistent with the research by Imboden et al 34 ; in adults with depression disorders, the volume reduction of the hippocampus, anterior cingulate cortex, prefrontal cortex, striatum, and amygdala and the impairment of white matter integrity are often observed.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…14 In addition, a recent study of exercise programs has shown that exercise can significantly reduce depression scores. 33 Collectively, the results of this study suggest that AG alone and the therapy of AG combined with AE can alleviate depressive symptoms in MSD patients, and the efficacy of AG + AE may be better than that of AG alone. This is consistent with the research by Imboden et al 34 ; in adults with depression disorders, the volume reduction of the hippocampus, anterior cingulate cortex, prefrontal cortex, striatum, and amygdala and the impairment of white matter integrity are often observed.…”
Section: Discussionmentioning
confidence: 61%
“…It has been reflected that AG is effective in the treatment of MSD, with significant reductions in HAM-D and SHAPS scores from baseline to endpoint 14 . In addition, a recent study of exercise programs has shown that exercise can significantly reduce depression scores 33 . Collectively, the results of this study suggest that AG alone and the therapy of AG combined with AE can alleviate depressive symptoms in MSD patients, and the efficacy of AG + AE may be better than that of AG alone.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, personal wellbeing and life satisfaction, showing itself as a promoter of health effects and on the other hand, Pickleball as an agent with preventive effects by reducing depression symptoms, indicating high values in its participants in both directions. Similarly, to other physical-sport activities, where higher frequency of physical activity leads to increased mental health ( Murphy et al, 2022 ; Nweke et al, 2022 ; Shaw et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, we noted that several clinical trials focused on HAND reported significant rates of pre-intervention attrition. [30][31][32][33][34][35] One clinical trial testing cognitive rehabilitation therapy in people living with HIV found that 49.6% (59/119) who met the criteria for HAND then declined to be randomized into the trial. 30 Another computer-delivered cognitive training randomized controlled trial (RCT) found 25.4% (14/55) of participants receiving a Mild Neurocognitive Disorder HAND diagnosis chose not to continue with randomization.…”
Section: Implications For Clinical Trialsmentioning
confidence: 99%